2014
DOI: 10.1111/aos.12457
|View full text |Cite
|
Sign up to set email alerts
|

One‐year outcome of two different initial dosing regimens of intravitreal ranibizumab for myopic choroidal neovascularization

Abstract: ABSTRACT.Purpose: To evaluate and compare the 12-month outcomes of two different initial dosing regimens of intravitreal ranibizumab for myopic choroidal neovascularization (CNV). Methods: We retrospectively reviewed the medical records of 46 consecutive, treatment-naive eyes which received intravitreal ranibizumab for subfoveal and juxtafoveal CNV secondary to pathologic myopia with a follow-up of 12 months. Two groups were created according to different initial dosing regimens: group 1 included 25 eyes treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 28 publications
5
29
1
Order By: Relevance
“…However, Yang et al [26] were able to associate CNV recurrence with baseline CNV lesion size in eyes with mCNV treated with bevacizumab given as 1+ PRN. With regard to age, as in the present study, Kung et al [13] found no relationship between the need for retreatment and patient age.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…However, Yang et al [26] were able to associate CNV recurrence with baseline CNV lesion size in eyes with mCNV treated with bevacizumab given as 1+ PRN. With regard to age, as in the present study, Kung et al [13] found no relationship between the need for retreatment and patient age.…”
Section: Discussionsupporting
confidence: 58%
“…In their study [14] , the initial regimen (1+ vs. 3+) was not found to affect the need for retreatment or the number of retreatments required (2 ± 2.3 vs. 1.7 ± 2.1). In contrast, in the study by Kung et al [13] , patients treated initially with 1 or 3 monthly ranibizumab injections required 1.32 ± 1.22 or 0.57 ± 1.12 additional injections, respectively, over 1 year of follow-up. This meant that their 1+ PRN group required more additional treatments in the first year, which is similar to our observations (1.27 ± 0.96 and 0.46 ± 0.82).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations